CO-CREATION: POSITIONING DIFFERENT EXPERIENCES IN THE MULTIDIMENSIONAL SPACE - Reddy, Segar; Pandian, J Rajendran (PEOPLE: International Journal of Social Sciences, 2019)
The idea of co-creation has been applied by managers long before academic researchers started studying co-creation. de Koning, Crul & Wever, 2016 reviewed literature on over fifty models of co-creation and presented four meta-models by synthesizing the literature they reviewed. In our paper, our main focus is to position three different co-creation examples in the co-creation space presented by de Koning et al., 2016 in their meta-models. Our first step is to identify all independent dimensions in each meta-model and develop on multidimensional model of co-creation. Once we have developed the multidimensional model, then we could position the three cases in which we have some in-depth understanding of how co-creation is applied. The first case is the co-creation experience from SAP, the enterprise resource planning software provider and the co-creation efforts with its customers. The second is the experience from those using Adobe software and publishing their own creations. Adobe provides a space for these original creations and share these creations with other Adobe software users. The third case is an example of automobile producers working with their auxiliary suppliers and developing new components or parts which enhance the performance of the new automobile. Our attempt to position these co-creation cases is to understand whether any other additional dimension(s) is (are) required to describe the co-creation space and the spectrum of activities where co-creation takes place. From the experience we gain by applying the multidimensional model, we intend to make contributions in future based on in-depth studies to be conducted based on our learning from this exercise.